Gender-specific association of STON2 rs2371597 polymorphism in keratoconus patients of Saudi origin - Kondkar, Altaf A.; Sultan, Tahira; Azad, Taif A.; Khatlani, Tanvir; Lobo, Glenn P.; Kalantan, Hatem; Al-Obeidan, Saleh A.; Al-Muammar, Abdulrahman M. (Frontiers in Genetics, 2024)
ObjectiveTo investigate the association of specific genetic polymorphisms (rs2371597 in STON2, rs11720822 in PDIA5, rs387907358 in WNT1, and rs77542162 in ABCA6) in a Saudi cohort of keratoconus (KC) patients compared to controls.MethodsA retrospective case-control genetic association study was conducted. The study included 99 KC patients and 193 healthy controls. Genotyping was performed using real-time PCR with TaqMan assays. Associations between genetic polymorphisms and KC were assessed using various genetic models and binary logistic regression analysis.ResultsNone of the tested polymorphisms showed an overall association with KC risk. Specifically, the rs2371597 polymorphism in STON2 did not demonstrate a significant association with KC risk across different genetic models. However, a gender-specific effect of rs2371597 was noted: in men, the C/G genotype was associated with a higher risk of KC, particularly in the dominant model, while no significant association was observed in women. Age and sex were identified as significant predictors of KC risk, but rs2371597 did not significantly affect KC risk in regression analysis.ConclusionPreliminary evidence suggests a gender-specific effect of the rs2371597 polymorphism in STON2, with an increased KC risk associated with C/G-C/C genotypes in men which was age-dependent. This result highlights the importance of considering population-specific genetic factors and the potential gender-specific effects on KC susceptibility. However, these findings need further validation with larger age- and sex-matched samples of diverse populations.